Effect of vitamin D on athletic performance - a systematic review - Maai, N.; Frank, F. A.; Meuris, A.; Ferreira, N. (Journal of Human Sport & Exercise, 2025)
Vitamin D is essential for optimal athletic performance; however, the evidence for its effect on athletic performance remains inconclusive. This systematic review aimed to investigate the effect of vitamin D supplementation on athletic performance in athletes. A comprehensive and systematic search of six electronic databases was conducted in accordance with PRISMA reporting guidelines, using a combination of Boolean operators and MeSH keywords. A total of 13 studies were included in the review. The included studies demonstrated that vitamin D supplementation consistently elevates serum 25(OH)D levels in athletes. A subset of the included studies reported significant improvements in athletic performance following the administration of vitamin D supplements, particularly in those athletes with low vitamin D status initially. Another cluster of studies focused on the effects of vitamin D supplementation on parameters of haematological and muscle recovery, with mixed results. Additionally, there were observations of seasonal fluctuations in vitamin D levels, which highlight the importance of considering the timing of supplementation. Vitamin D supplementation has been linked to improved athletic performance, particularly in athletes with low initial vitamin D status. However, the impact of this intervention is influenced by individual characteristics, the type of exercise, and the specific dosage and duration of supplementation. To gain a more comprehensive understanding of the mechanisms and optimal protocols for vitamin D supplementation in athletes, further research is required.